Insulin-like growth factor 1 supplementation supports motor coordination and affects myelination in preterm pigs - Christiansen, Line I.; Ventura, Gemma C.; Holmqvist, Bo; Aasmul-Olsen, Karoline; Lindholm, Sandy E. H.; Lycas, Matthew D.; Mori, Yuki; Secher, Jan Bojsen-Møller; Burrin, Douglas G.; Thymann, Thomas; Sangild, Per T.; Pankratova, Stanislava (Frontiers in neuroscience, 2023)
Preterm infants have increased risk of impaired neurodevelopment to which reduced systemic levels of insulin-like growth factor 1 (IGF-1) in the weeks after birth may play a role. Hence, we hypothesized that postnatal IGF-1 supplementation would improve brain development in preterm pigs, used as a model for preterm infants. Preterm pigs delivered by cesarean section received recombinant human IGF-1/IGF binding protein-3 complex (rhIGF-1/rhIGFBP-3, 2.25 mg/kg/day) or vehicle from birth to postnatal day 19. Motor function and cognition were assessed by monitoring of in-cage and open field activities, balance beam test, gait parameters, novel object recognition and operant conditioning tests. Collected brains were subject to magnetic resonance imaging (MRI), immunohistochemistry, gene expression analyses and protein synthesis measurements. The IGF-1 treatment increased cerebellar protein synthesis rates (both and ). Performance in the balance beam test was improved by IGF-1 but not in other neurofunctional tests. The treatment decreased total and relative caudate nucleus weights, without any effects to total brain weight or grey/white matter volumes. Supplementation with IGF-1 reduced myelination in caudate nucleus, cerebellum, and white matter regions and decreased hilar synapse formation, without effects to oligodendrocyte maturation or neuron differentiation. Gene expression analyses indicated enhanced maturation of the GABAergic system in the caudate nucleus (decreased ratio) with limited effects in cerebellum or hippocampus. Supplemental IGF-1 during the first three weeks after preterm birth may support motor function by enhancing GABAergic maturation in the caudate nucleus, despite reduced myelination. Supplemental IGF-1 may support postnatal brain development in preterm infants, but more studies are required to identify optimal treatment regimens for subgroups of very or extremely preterm infants.